Adherence to higher Life's Essential 8 scores is linearly associated with reduced all-cause and cardiovascular mortality among US adults with metabolic syndrome: Results from NHANES 2005-2018. - Dao-Cheng Zhou; Jia-Lin Liang; Xin-Yu Hu; Hong-Cheng Fang; De-Liang Liu; Heng-Xia Zhao; Hui-Lin Li; Wen-Hua Xu (PLoS ONE)
Background Life's Essential 8 (LE8) is the American Heart Association (AHA)'s recently updated assessment of cardiovascular health (CVH). Metabolic syndrome (MetS) is one of the most common chronic noncommunicable diseases associated with CVH impairment and an increased risk of mortality. However, the association of LE8 with all-cause and disease-specific mortality in the MetS population remains unknown. We aimed to explore these associations in a national prospective cohort study from NHANES 2005-2018. Methods The LE8 was calculated according to the assessment criteria proposed by the AHA, which includes health behavior and health factor domains. LE8 scores were categorized as low CVH (0-49), moderate CVH (50-79), and high CVH (80-100). MetS was assessed according to NCEP-ATP III criteria, and mortality data were obtained through prospective linkage to the National Death Index database. Results 7839 participants with MetS were included and only 3.5% were in high CVH. In the fully adjusted models, LE8 was negatively associated with both all-cause and cardiovascular disease (CVD) mortality (hazard ratios [HR] and 95% confidence intervals [CI] of 0.978 (0.971,0.984) and 0.972 (0.961,0.984), respectively, both p < 0.0001). Both moderate/high CVH were associated with significantly lower mortality compared to low CVH (both p for trend <0.0001). Health behaviors had a more dominant effect compared to health factors. All-cause and CVD mortality gradually decreased with increasing ideal LE8 metrics. LE8 was not significantly associated with cancer mortality. LE8 and health behaviors were linearly associated with all-cause and CVD mortality, whereas health factors were nonlinearly associated (plateaued after ≥50). Education and chronic kidney disease influenced the association of LE8 with all-cause and CVD mortality, respectively. Conclusions LE8 scores were negatively associated with all-cause and CVD mortality in the MetS population, while health behaviors had a dominant role. Adherence to higher CVH contributes to the prevention of excessive all-cause and CVD mortality in the MetS population.